The Circulation Network of East Asian Television Dramas in Indonesia: Television and Pirated DVDs as Intermediaries - Tambunan, Shuri Mariasih Gietty (UI Scholars Hub, 2014)
East Asian television dramas from Japan, Taiwan and South Korea have become a significant part of the cultural globalization process in the Indonesian mediascapes since the 1990s. The Indonesian cultural, political and social specificities have created significant distinctions on how these television dramas reconstruct the shared imagination of (East) Asia in comparison with how it is in other locales. The research findings have extended the discussion of geocultural/linguistic regions, which argues that the success of a television drama in one region, for example telenovelas in Latin America, is affected by a similar cultural and linguistic background. It echoes that the Asian case should be analyzed in a distinctive framework compared to other regional case studies, specifically in the circulation and distribution process. The research concerns a multi-layered analysis that draws on the methodological resources of textual analysis and institutional research, which contextualized these television dramas culturally, historically and geographically. The aim is to understand how the two primary media technologies in the in-between space of production and consumption, namely television and pirated DVDs, work as intermediaries and also as gatekeepers since they precondition commonalities between these television dramas with local expectations. Drama televisi dari Jepang, Taiwan dan Korea Selatan telah menjadi bagian dari proses globalisasi budaya di Indonesia sejak tahun 1990an. Indonesia memiliki konteks budaya, politik dan sosial yang spesifik sehingga ada perbedaan yang signifikan dalam proses pemaknaan drama televisi ini dalam hubungannya dengan bagaimana imaginasi mengenai ‘Asia’ (Timur) dilakukan di Indonesia apabila dibandingkan dengan negara lain. Hasil penelitian pada akhirnya mengembangkan diskusi mengenai wilayah geocultural/linguistik yang mengasumsikan bahwa kesuksesan drama televisi di sebuah wilayah, misalnya Amerika Latin, dilatarbelakangi persamaan budaya dan sistem linguistik. Maka dari itu, studi kasus ini, yang terjadi di wilayah regional Asia, harus dianalisa dengan kerangka pemikiran yang berbeda dibandingkan dengan studi kasus di wilayah regional lainnya terutama dalam proses sirkulasi dan distribusi. Penelitian ini menggunakan beberapa metode seperti analisis tekstual dan studi institusional yang memposisikan drama televisi dari negara Asia Timus sesuai dengan konteks budaya, sejarah dan geografinya. Tujuan utama penelitian ini adalah memaknai bagaimana dua mediateknologi, televisi dan DVD bajakan, bekerja sebagai intermediaries dan juga sebagai gatekeepers ketika kedua media ini mengkonstruksikan commonalities (asumsi bahwa adanya persamaan antara apa yang ditampilkan di drama televisi dengan konteks lokal Indonesia).